TRATAMENTO PARA CONTROLE DE MELASMA - Maciel, Amanda Antunes; Dal Piva, Emanuelly Cristina; Lima, Gabrielli Pinheiro; Serpa, Elaine Cristina de Sousa Neves (Anais de Saúde Coletiva; v. 2 n. 2 (2022): 2022/2, 2023)
Tratamento para Controle de melasma. Estética facial. Autoestima.